Phosphorus fertilization requirement of supplemental feed-fed nile tilapia (Oreochromis nitoticus) ponds - Moe Thidar Oo; Yi, Yang; Yakupitiyage, Amararatne; Thakur, Dhirendra Prasad; Lin, C. Kwei; Joint Japan; World Bank Graduate Scholarship Program (JJ/WBGSP); AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
An experiment was conducted in fifteen 200-m2 earthen ponds at the Asian Institute of Technology, Thailand during September 2005 to January 2006. The objectives of this study were to determine the effects of different rates of phosphorus fertilizer application on Nile tilapia production, pond water quality parameters, nutrient utilization efficiency under supplemental feeding, and to evaluate the cost and return of tilapia production in fed ponds fertilized at different phosphorus rates. Five phosphorus fertilization rates were used as treatments in a randomized completely block design: 100%, 75%, 50%, 25% and 0% of 7 kg P ha-1 wk-1. Nitrogen fertilization rate was fixed at 28 kg N ha-1wk-1 for all the treatments throughout the experiment. Sex-reversed all-male Nile tilapia about 100 g size were stocked at 3 fish m and fed at 50% satiation feeding rate in all ponds. Mean weight, mean weight gain, daily weight gain and net yield were not significantly different among treatments (P>0.05). Water quality parameters were not significantly different among treatments, except total Kjeldahl nitrogen, total phosphorus and soluble reactive phosphorus. Nutrient budget showed that higher rates of phosphorus fertilizer input resulted in higher phosphorus sink in the sediment. Economic analysis showed that all the treatments with phosphorus fertilization resulted in positive net returns. Gross income was not affected by different phosphorus fertilization rates. Treatment with 25% phosphorus fertilization might be used as an alternative strategy of Nile tilapia pond culture in terms of economic return and nutrient loss in sediment
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2006
Keywords: Nile tilapia